Growth and Reproductive Biology of Shilluk, Leuciscus vorax (Heckel, 1843), in the Third River / central Iraq - Jawad Lafat Al-Zaidy , Kadhim (The Indian Journal of Animal Reproduction, 2026)
This study was conducted on several environmental parameters, and some reproduction physiological processes of the Shilluk fish Leuciscus vorax were conducted alongside the Third River throughout central Iraq between the months of January and December of 2022. The results indicated that the temperatures of the water ranged from 10.1°C in January to 34.7°C throughout July. Every month, the acidity value varied between 6.4 and 8.3. The total dissolved solids (T.D.S.) average each month varied between 4.04 ppt and 7.41 ppt. The oxygen content in the solution varied between 9.22 and 6.9 mg/L. Throughout the course of the research, data from 106 L. vorax specimens were gathered. The hormonal Gonadosomatic Index (GSI) as well as the formation of gonads was examined in order to estimate the fertilization time. The results show that this kind of organism undergoes one reproductive cycle annually, with spawning events taking place between the months of January and February. The overall length (TL) of the individuals varied from 10.83 to 53.1 cm. Comparative reproductive estimates varied between 63388 to 79695 eggs per kilogram of weight of the person, and eggs lengths at maximal maturation varied from 1.5 to 1.64 mm.
Keywords: Water quality; Gonadosomatic index; Relative fecundity